Towards a comprehensive and interoperable representation of consent-based data usage permissions in the German medical informatics initiative - Bild, Raffael; Bialke, Martin; Buckow, Karoline; Ganslandt, Thomas; Ihrig, Kristina; Jahns, Roland; Merzweiler, Angela; Roschka, Sybille; Schreiweis, Björn; Stäubert, Sebastian; Zenker, Sven; Prasser, Fabian (BMC medical informatics and decision making, 2020)
The aim of the German Medical Informatics Initiative is to establish a national infrastructure for integrating and sharing health data. To this, Data Integration Centers are set up at university medical centers, which address data harmonization, information security and data protection. To capture patient consent, a common informed consent template has been developed. It consists of different modules addressing permissions for using data and biosamples. On the technical level, a common digital representation of information from signed consent templates is needed. As the partners in the initiative are free to adopt different solutions for managing consent information (e.g. IHE BPPC or HL7 FHIR Consent Resources), we had to develop an interoperability layer.